Analysis on the Implementation of Iron Supplementation Program by Midwives at Primary Healthcare Center in South Minahasa District - Sjenny Olga Tuju; Sri Achadi Nugraheni; Lucia Ratna Kartika (Jurnal Manajemen Kesehatan Indonesia, 2013)
Pelaksanaan program pemberian tablet Fe (besi) di Puskesmas Kabupaten Minahasa Selatan masih dibawah target nasional (78,8 %) target Nasional (90 %) walaupun sudah ada kebijakan tentang program pemberian tablet Fe (besi) pada bidan.  Survey pendahuluan yang dlakukan oleh 7 bidan di 7 Puskesmas diperoleh informasi bahwa masih ada bidan yang belum melaksanakan sesuai dengan standar operasional prosedur yang sudah ada. Penelitian ini bertujuan untuk menganalisis faktor yang mempengaruhi implementasi program pemberian tablet Fe (besi) oleh bidan di Puskesmas Wilayah Kabupaten Minahasa Selatan. Jenis penelitian merupakan deskriptif observasional analitik dengan pendekatan cross sectional.Pengumpulan  data  dilakukan  wawancara  kuesioner  dan  observasi  langsung  pada  saat  bidan memberikan  tablet  Fe  (besi)  di  polindes/Posyandu.  Jumlah  sampel  98  orang  bidan  desa  di  17 kecamatan  Kabupaten  Minahasa  Selatan.yang  diambil  secara Simple  Random  Sapling. Analisis univariat, bivariat dilakukan dengan chi-square test dan analisis multivariat dengan regresi logistik Bidan  sudah  melaksanakan  kegiatan-kegiatan  dengan  kategori  baik  dalam  komunikasi (46,9%),Sumberdaya  (52%),Disposisi  (57,1%)  dan  Struktur  Birokrasi  (53,1%).  variabel  yang berpengaruh terhadap implementasi program pemberian tablet Fe (besi) adalah birokrasi (nilai p=0,24 ) exp ß=2,584.Saran untuk Dinas Kesehatan Kabupaten Minahasa Selatan adalah : memberikan soaialisasi kepada bidan tentang manfaat dari pengunaan Standar Operasional Prosedur (SOP) pemberian tablet Fe(besi).  Memberikan  insentif  bagi  bidan  yang  telah  melaksanakan  sesuai  dengan  standar  yangmemenuhi cakupan, diberikan Hb Sahli set bagi semua bidan yang bertugas didesa yang belum mempunyai lat tersebutImplementation of iron tablets supplementation program in the primary healthcare centers of South Minahasa district was still below the national target (78.8%) although there was a policy regarding iron  supplementation  program  by  midwives.  The  national  target  was  90%.  Preliminary  survey conducted on 7 midwives showed that there were midwives who had not implemented the program according to the existed standard operating procedure. The objective of this study was to analyze factors affecting the implementation of iron tablets supplementation program by midwives in the primary healthcare centers in the area of South Minahasa district. This  was  an  observational  analytical  study  with  cross  sectional  approach.  Data collection  was done through interview guided by questionnaire and direct observation to midwives when giving iron tablets in a polindes/posyandu. The number of study samples was 98 village midwives in 17 sub districts of South Minahasa district. They were selected using simple random sampling method. Univariate analysis, bivariate analysis with chi square test, and multivariate analysis with logistic regression were applied in the data analysis. Results of the study showed that midwives had implemented the activities with good category incommunication (46.9%), resources (52%), disposition (57.1%), and structured bureaucracy (53.1%).Variable affecting the implementation of iron tablets supplementation program was bureaucracy (p= 0.24), exp â= 2.584.Suggestions for the South Minahasa district health office were to conduct socialization to midwives regarding the benefits of using standard operating procedures of the implementation of iron tables supplementation;  to  give  incentive  for  midwives  who  implement  the  program  according  to  the standard and reaching the target; to provide Hb Sahli set for all midwives who work in the village and they do not have the Hb Sahli set.